Deaf Interpreters at Work : International Insights - Metzger, Melanie; Collins, Steven D.; Stone, Christopher; Adam, Robert (Research Associate) (Studies in interpretation (Washington, D.C.), 2014)
Now, for the first time, a collection featuring 17 widely respected scholars depicts the everyday practices of deaf interpreters in their respective nations. Deaf Interpreters at Work: International Insights presents the history of Deaf translators and interpreters and details the development of testing and accreditation to raise their professional profiles. Other chapters delineate the cognitive processes of Deaf interpreting; Deaf-Deaf interpreter teams; Deaf and hearing team preparation; the use of Tactile American Sign Language by those interpreting for the Deaf-Blind community; and conference interpreting and interpreting teams. Along with volume coeditors Robert Adam, Christopher Stone, and Steven D. Collins, contributors include Markus Aro, Karen Bontempo, Juan Carlos Druetta, Senan Dunne, Eileen Forestal, Della Goswell, Juli af Klintberg, Patricia Levitzke-Gray, Jemina Napier, Brenda Nicodemus, Debra Russell, Stephanie Sforza, Marty Taylor, and Linda Warby. The scope of their research spans the world, including many unique facets of interpreting by deaf people in Argentina, Australia, Canada, England, Finland, Ireland, Sweden, and the United States, establishing this work as the standard in this burgeoning discipline.